2015
DOI: 10.5670/oceanog.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Technology for Ocean Acidification Research: Needs and Availability

Abstract: Diverse instruments, both custom built and commercially available, have been used to measure the properties of the aqueous CO 2 system in seawater at differing levels of autonomy (automated benchtop, continuous underway, autonomous in situ). In this review, we compare the capabilities of commercially available instruments with the needs of oceanographers in order to highlight major shortfalls in the state-of-the art instrumentation broadly available to the ocean acidification (OA) scientific community. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…In recent years, a number of in situ sensors for carbonate chemistry have become commercially available, making autonomous measurements more accessible to the community [31]. These sensors allow for routine deployments in a wide range of ecosystems by research groups that are not necessarily experts in instrumentation.…”
Section: Compact Fixed Observatoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of in situ sensors for carbonate chemistry have become commercially available, making autonomous measurements more accessible to the community [31]. These sensors allow for routine deployments in a wide range of ecosystems by research groups that are not necessarily experts in instrumentation.…”
Section: Compact Fixed Observatoriesmentioning
confidence: 99%
“…In this review, we summarize work from the past 5 years highlighting the expansion of our autonomous carbonate observing capabilities, and some of the key recent scientific discoveries. Recent reviews have highlighted advances in carbonate sensor technology [31,32] so we instead focus on the autonomous instrumentation that currently comprises our carbonate observation network and promising emerging technologies. In this paper, we review (1) current autonomous observational capabilities, (2) emerging sensors and autonomous platforms for carbonate observations, and (3) challenges for the measurement and interpretation of these novel observations.…”
Section: Introductionmentioning
confidence: 99%
“…These instruments permit continuous in-situ pH measurements, one of the four measureable carbonate system parameters. p CO 2 can also be accurately measured in situ using autonomous instrumentation [17, 18]. While the remaining carbonate parameters can be calculated from measurements of pH and p CO 2 , this particular combination is susceptible to large calculation error derived from the measurement error for each respective parameter [19].…”
Section: Introductionmentioning
confidence: 99%
“…The Alliance for Coastal Technologies (ACT; http://www.act-us.info/) and the International Ocean Carbon Coordination Project (http://www.ioccp.org) have been promoting shared databases and intercomparison studies of underway p CO 2 systems as well as for other carbon system measurements. Martz et al () identified a general lack of documentation of measurement systems in the peer‐reviewed literature and the need to “conduct international intercomparison exercises” and “promote availability of instrumentation”.…”
mentioning
confidence: 99%